Pemberdayaan Masyarakat melalui Inovasi Media Tanam Jamur Tiram dari Limbah Serbuk Kayu - Kheva Adnandhyto; Nuari Shinta Devi; Labibah Putri Alifah; Felina Arfiana; Muhammad Rauf Dermawan (CV. ITTC INDONESIA, 2025)
The utilization of abundant sawdust waste in Bulakan Subdistrict, Sukoharjo Regency, has become a crucial issue in both environmental conservation and community welfare improvement. This area is known as a center for woodcraft industries that produce large quantities of sawdust, which has so far been used merely as fuel. This situation became the focus of a community empowerment activity aimed at educating and optimizing the use of sawdust waste as an alternative growing medium for oyster mushroom cultivation. The activity employed a combination of socialization and hands-on practice, conducted on March 8, 2025. The outcomes aligned with the objectives, as demonstrated by the enthusiasm and active participation of the attendees. This suggests that practice-based education using a participatory approach is more effective in enhancing public understanding and skills. This innovation not only supports sustainable agriculture but also creates new entrepreneurial opportunities for the local community.